Analisis Penerapan Sistem Informasi Qiospay Dalam Meningkatkan Prediktivitas Penjualan Pulsa Pada Konter H3 Di Dusun Buadao, Desa Bambu - Muh.Haizal Asmin; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the implementation of the Qiospay information system in enhancing sales predictability at H3 Counter located in Buadao Hamlet, Bambu Village. Qiospay is a PPOP-based digital service application that provides real-time transactions for mobile credit top-ups, data packages, electricity tokens, and various other payment services. In the context of micro-enterprises, the ability of an information system to generate sales predictions, transaction histories, and accurate recording data is a crucial factor in supporting business planning and decision-making processes. This research employs a descriptive method with a qualitative approach through observation, interviews, and documentation studies. The results indicate that the use of Qiospay assists the counter owner in predicting digital stock requirements, identifying customer transaction patterns, and improving the accuracy of business planning. Therefore, the implementation of Qiospay makes a significant contribution to improving sales predictability at H3 Counter.